Enhancing the Welfare of Non-Permanent Teachers in the Sumenep Islands: The Imperative for Regional Regulations - Mukhlishi Mukhlishi; Yetti Hidayatillah; Supandi Supandi; Khoirul Asiah; Choli Astutik; Hasan Basri; Sama' Sama' (AL-ISHLAH: Jurnal Pendidikan, 2024)
Non-permanent teachers, in carrying out their duties and responsibilities as educators and instructors, have the right to earn income above the minimum living standards and social welfare guarantees. Teachers highly anticipate the issuance of regional regulations in the field of education in an effort to improve the welfare of teachers in Sumenep. This research aims to determine the urgency of regional regulations for improving the welfare of non-permanent teachers in the Sumenep Islands. This research uses a qualitative approach, which is a descriptive analysis with a case study type. Informants were determined using the purposive sampling method, and the informants in this study were 7 school principals, 25 honorary teachers, and seven salary treasurers. Data collection used three methods, namely, interviews, observation, and documentation. The collected data was analyzed using an interactive analysis model. According to the study's findings, the pay for non-permanent teachers as a whole is still below the minimum living standards set in the Sumenep region. Teachers do not always hope to be able to take part in the civil service selection so that teachers' minimum living needs can be met and social welfare can be guaranteed.